An Essay on the Subjective Valuation of an Incentive System in an Insurance Market - Mahito, Okura; Hiroyuki, Nozaki (Journal of Mathematical Economics and Finance; Vol 2 No 2 (2016): JMEF Volume II, Issue 2(3), Winter 2016, 2017)
This study discusses two discount systems, namely, the insurance pre- mium discount system, where the policyholder’s valuation is objective, and the book price discount system, where the policyholder’s valuation is subjective. The main pur- pose of this study is to compare these discount systems and show the conditions under which each discount system is chosen by an insurance firm. The main conclusions of this study are as follows. First, the insurance firm chooses the book price discount (insurance premium discount) system if the policyholder’s disutility of loss prevention effort is relatively high (low). Second, the insurance firm chooses the book price discount system when the initial wealth and maximum subjec- tive valuation of the book price discount are large. The insurance firm also chooses the book price discount system when the insurance premium, the amount of damage and effect of the loss prevention effort are small.